The relationship between coach’s personality traits and the cohesion of football team - Lebad, Maamar; Rouini, Ahmed (Journal of Human Sciences, 2022)
The cohesion of football team, for this purpose, we applied the descriptive approach a linking, On a sample composed of 60 coaches and 900 players representing 60 teams in some provinces of Algerian east ( Batna, Constantine, Oum El-Bouaghi. Khenchela, Tebessa). For the sport season 2018/2019. The researcher used the Fribourg Questionnaire of Personality Traits translate in Arabic by Hassan Allaoui 1998, and the Cohesion Team Questionnaire designed by Hassan Allaoui 1994. For statistical processing we used SPSS, while the results revealed that there is a Strong positive significant correlations (p<0.05) between the cohesion of football teams and social and calm traits, also the results showed opposite significant correlations (p<0.05) with nervousness and aggression traits.In light of these results the study recommends a number of recommendations the most important is attention to the social aspect of the sportive team and use the democratic leadership style.